2014
DOI: 10.1002/hed.23595
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic robot‐assisted neck dissection via a retroauricular or modified facelift approach in head and neck cancer: A comparative study with conventional transcervical neck dissection

Abstract: Therapeutic RAND via a retroauricular or modified facelift approach was successful with satisfactory esthetic results in patients with node-positive head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 21 publications
(48 reference statements)
5
58
0
1
Order By: Relevance
“…Therefore, to overcome the limitations mentioned above, robot-assisted radical or selective neck dissections via a retroauricular approach or a modified face-lift approach have been reported. 97, 98, 99, 100, 101, 102, 103, 104, 105, 106 The results suggested that the robot-assisted surgery lasted longer than conventional surgery, but the intraoperative bleeding, lymph node retrieval, volume of drainage, hospitalization and related complications of robot-assisted neck dissection (RAND) were similar to those of open neck dissection. Furthermore, the patients who underwent robotic surgery were much more satisfied with the postsurgical aesthetics than those who underwent open surgery.…”
Section: Clinical Applications Of Robotic Surgery In the Head And Neckmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to overcome the limitations mentioned above, robot-assisted radical or selective neck dissections via a retroauricular approach or a modified face-lift approach have been reported. 97, 98, 99, 100, 101, 102, 103, 104, 105, 106 The results suggested that the robot-assisted surgery lasted longer than conventional surgery, but the intraoperative bleeding, lymph node retrieval, volume of drainage, hospitalization and related complications of robot-assisted neck dissection (RAND) were similar to those of open neck dissection. Furthermore, the patients who underwent robotic surgery were much more satisfied with the postsurgical aesthetics than those who underwent open surgery.…”
Section: Clinical Applications Of Robotic Surgery In the Head And Neckmentioning
confidence: 99%
“…Furthermore, the patients who underwent robotic surgery were much more satisfied with the postsurgical aesthetics than those who underwent open surgery. Additionally, the study of Kim et al 100 and Tae et al. 105 demonstrated that RAND may have a lower risk of lymphedema and lymph node recurrence than conventional neck dissection.…”
Section: Clinical Applications Of Robotic Surgery In the Head And Neckmentioning
confidence: 99%
“…Park, et al [6] did not perform RRAND in patients with pathological lymph nodes, while in a separate report Park, et al [7] performed RRAND only on N0 and N1 necks. Kim, et al [8] did not consider extracapsular spread in the lymph nodes as a definite contraindication. In the spread of the primary tumor, many authors did not find it appropriate to use RRAND for advanced stage tumors.…”
Section: Preoperative Evaluationmentioning
confidence: 99%
“…In the spread of the primary tumor, many authors did not find it appropriate to use RRAND for advanced stage tumors. However, Kim, et al [8] reported that the procedure was appropriate except in unrespectable tumors. The same authors also did not accept prior radiotherapy for nasopharyngeal carcinoma as a contraindication.…”
Section: Preoperative Evaluationmentioning
confidence: 99%
See 1 more Smart Citation